Thermal conductivity of solid oxygen, nitrogen, and their solid solutions - Freiman, Yu.A.; Sumarokov, V.V.; Owski, A. Jez.; Stachowiak, P.; Mucha, J. (Физика низких температур, 1996)
This work was supported in part by the Polish State Committee for Scientific Research (Grant 2 0388 91 01) and in part by International Science Foundation (Grants U9N000 and U9N200).